Retirement as a lens for socioeconomic differences in Cognition and well-being - König, Stefanie; Lindwall, Magnus; Henning, Georg; Johansson, Boo (Nordic Journal of Working Life Studies, 2018)
This study conceptualizes retirement as a lens with regard to patterns of social inequality across the life course. It investigates if socioeconomic differences in well-being and cognitive performance differ between older workers and retirees, using data from the HEARTS (Health, Aging and Retire- ment Transitions in Sweden) study. The results provide evidence for retirement as a positive lenswith regard to cognition, following the ‘use it or lose it’ hypothesis. We also find evidence for retire- ment as a negative lens with regard to well-being, supporting the cumulative (dis-)advantages theory.We test different aspects of socioeconomic status, that is, education, income, occupationalgroup, and subjective work aspects and find the strongest effects for education. Hence, this studycontributes with an understanding of mechanisms behind social inequalities over the life-course by using retirement and the loss of the work role as a marker for potential change